PENYELESAIAN SENGKETA EKONOMI SYARIAH BERBASIS BUDAYA HUKUM - SA’ADAH, SA’ADAH (At-Taradhi, 2014)
Settlement of sharia economic disputes on Islamic financial institutions can be done through the judiciary (litigation) or outside the judiciary (non-litigation). With the new authority, the religious courts are required to prepare the facilitiy and infrastructure, and Human Resources in order to handle Islamic economic disputes, which is submitted to the religious courts. Islamic economics in the settlement of disputes in religious courts, legal culture also affect the judges decision as well. for example, Islamic religion become a foothold in solving all the problems posed to the religious court. In connection with this, this paper will describe how the legal culture, in this case religion and education, gives effect to the settlement of Islamic economics disputes in the religiousÂ court.